2003
DOI: 10.1002/ace.86
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of high‐quality intensive courses

Abstract: Intensive courses have become a mainstay of higher education. Defined as semester-or quarter-equivalent classes offered in compressed, accelerated, or condensed formats, most colleges and universities now offer intensive classes alongside traditional semester-length classes. Although intensive courses have become quite common, many academic and administrative pundits condemn their use and claim that these formats sacrifice academic rigor and learning for student convenience and higher enrollments. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 7 publications
2
64
0
1
Order By: Relevance
“…Our thematic analysis highlighted that FSS students experienced less stress in the summer as a result of smaller class numbers and more individual attention from the lecturer. This supports previous research that less stress is experienced in smaller groups (Bandiera et al, 2010) and that students experience higher overall student satisfaction with smaller classes (Ferguson & DeFelice, 2010;Scott, 2003). Additionally, our finding of more focus in summer due to fewer courses being taken concurs with research that increased course load leads to greater student stress (see Nasiri & Shokrpour, 2012;Yang, 2004) which implies that less course load is more manageable and therefore less stressful.…”
Section: Stress Associated With Condensed Summer School Courses Versusupporting
confidence: 81%
See 2 more Smart Citations
“…Our thematic analysis highlighted that FSS students experienced less stress in the summer as a result of smaller class numbers and more individual attention from the lecturer. This supports previous research that less stress is experienced in smaller groups (Bandiera et al, 2010) and that students experience higher overall student satisfaction with smaller classes (Ferguson & DeFelice, 2010;Scott, 2003). Additionally, our finding of more focus in summer due to fewer courses being taken concurs with research that increased course load leads to greater student stress (see Nasiri & Shokrpour, 2012;Yang, 2004) which implies that less course load is more manageable and therefore less stressful.…”
Section: Stress Associated With Condensed Summer School Courses Versusupporting
confidence: 81%
“…Second, semester courses carry more group projects, which Burns and Sinfield (2008) contend can result in serious conflicts. These factors influence student focus (Scott, 2003). Finally, UWI semester courses always carry much larger class numbers which can result in more stress (see Agolla & Ongori, 2009;Bandiera, et al, 2010), and arguably less effective student-teacher interactions (Austin & Gustafason, 2006).…”
Section: Stress Associated With Condensed Summer School Courses Versumentioning
confidence: 99%
See 1 more Smart Citation
“…Anastasi (2007), in contrast, found that student ratings of instructors were similar across the two conditions, although they rated the intensive short courses as more challenging. Scott (2003) suggests student satisfaction is highly dependent upon the skill of the instructor, arguing that it is important to establish an atmosphere and relationships early in a short course to help students stay focused and perform better. While Scott (2003) was referring to face-to-face courses, it is plausible to suggest online instructors might need to be similarly prepared to adapt their instruction to an accelerated schedule.…”
Section: Course Lengthmentioning
confidence: 99%
“…In particular, they proposed instructors set clear learning outcomes, recognize individual learning differences, create positive classroom environments, consider using short, frequent assignments, and provide regular feedback and support to students. Building on her earlier work, Scott (2003) reported on her research findings, and those of others, concluding that there are benefits of intensive courses such as more focused learning, more collegial classroom relationships, more in-depth discussions, and stronger academic performance when certain instructional and classroom attributes are present. These attributes include instructor enthusiasm, active classroom interaction, good course organization, and relaxed learning environments.…”
Section: Teaching Courses In Compressed Formatsmentioning
confidence: 99%